Mapalus Sebagai Model Relasi Solidaritas Kristen Dan Islam - Manoppo, Yemima Imelda Margareth; Mawuntu, Marhaeni Luciana (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article discusses how Mapalus can be a model of Christian-Islamic solidarity relations in Tombatu Dua and Tombatu Tiga Tengah Villages. The relationship between Christianity and Islam within the scope of the Christian majority has its own uniqueness that can be found. The research was conducted using a qualitative method with a phenomenological approach combined with anthropology. Phenomenological research combined with anthropology is carried out using a phenomenological framework as a research approach and anthropology as a discipline that studies humans and their cultures. By focusing on cooperation and respect for each other, Mapalus provides inspiration on how to foster brotherhood between religious communities. Mapalus culture is a capital of solidarity between religious communities because it embodies the principles of diversity, togetherness, and tolerance.